2000
DOI: 10.1046/j.1460-9568.2000.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in preproenkephalin and adenosine‐2a receptor mRNA, but not preprotachykinin mRNA correlate with occurrence of dyskinesia in normal monkeys chronically treated with l‐DOPA

Abstract: Chronic treatment with L-DOPA induces dyskinesia in patients with Parkinson's disease (PD) and 1-methyl-4-phenyl-1,2,3, 6-tetrahydropyridine (MPTP)-treated monkeys, but is not thought to do so in normal humans or primates. However, we have shown that chronic oral high dose L-DOPA administration, with the peripheral decarboxylase inhibitor, carbidopa and with or without the peripherally acting catechol-O-methyl transferase (COMT) inhibitor, entacapone, to normal macaque monkeys for 13 weeks induced dyskinesia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 59 publications
(104 reference statements)
6
54
1
1
Order By: Relevance
“…It has been shown that neuropeptide mRNA levels of striatal preproenkephalin (PPE) and preprodynorphin (PPD) are increased in dyskinetic MPTP-lesioned monkeys compared to control MPTP-lesioned monkeys, similar to previous reports in the 6-OHDA lesioned parkinsonian rat (Gerfen et al, 1990;Zeng et al, 2000;Morissette et al, 2006;Guan et al, 2007;Tamim et al, 2010). Using opioid receptor-stimulated G-protein activation techniques, Chen and colleagues demonstrated that µ-opioid receptor-mediated G-protein activation is increased in the brain, specifically the cortex and basal ganglia in dyskinetic monkeys treated with LD.…”
Section: Other Chemical Systemssupporting
confidence: 86%
See 1 more Smart Citation
“…It has been shown that neuropeptide mRNA levels of striatal preproenkephalin (PPE) and preprodynorphin (PPD) are increased in dyskinetic MPTP-lesioned monkeys compared to control MPTP-lesioned monkeys, similar to previous reports in the 6-OHDA lesioned parkinsonian rat (Gerfen et al, 1990;Zeng et al, 2000;Morissette et al, 2006;Guan et al, 2007;Tamim et al, 2010). Using opioid receptor-stimulated G-protein activation techniques, Chen and colleagues demonstrated that µ-opioid receptor-mediated G-protein activation is increased in the brain, specifically the cortex and basal ganglia in dyskinetic monkeys treated with LD.…”
Section: Other Chemical Systemssupporting
confidence: 86%
“…LD treatment (Zeng et al, 2000). Recently, it had been shown that genetic knock-out of forebrain A2A receptors in mice can attenuate dyskinesias after LD treatment (Xiao et al, 2006).…”
mentioning
confidence: 99%
“…In addition, the interaction among A 2A and mGluR5 metabotropic glutamate receptors in the basal ganglia could also modulate psychostimulant-induced sensitization (Chiamulera et al, 2001). Changes in the expression of presumably postsynaptic A 2A Rs after repeated dopaminergic exposures might also play a functional role in the nucleus accumbens or dorsal striatum (Zeng et al, 2000;Calon et al, 2004;Tomiyama et al, 2004). Potential downstream postsynaptic mediators of sensitization that are also known to be regulated by the A 2A R include cytoplasmic signal transducers (eg dopamineand cAMP-regulated phosphoprotein of 32 kDa or DARPP-32) and nuclear transcriptional targets (eg DFosB, enkephalin, and dynorphin gene expression in striatal neurons; Fienberg et al, 1998;Canals et al, 2003;Lundblad et al, 2003;Hakansson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, with prolonged use of L-DOPA (over years), patients often develop involuntary movements called L-DOPAinduced dyskinesia (LID) (including chorea, athetosis, ballism, and dystonia), which can be disruptive and for some disabling (Chase, 1998;Obeso et al, 2000). Recently, adenosine A 2A receptors have been directly linked to L-DOPA-induced dyskinesia in humans and nonhuman primates (Zeng et al, 2000;Calon et al, 2004) and to models of LID in rodents (Fredduzzi et al, 2002;Tomiyama et al, 2004). CNS A 2A receptors are predominantly expressed in the basal ganglia, particularly in the striatum (Schiffmann et al, 1991).…”
Section: Introductionmentioning
confidence: 99%